Trade-offs between individual and ensemble forecasts of an emerging infectious disease - Rachel J. Oidtman (Nature Portfolio, 2021)
Newly emerged pathogens are inherently difficult to forecast, due to many unknowns about their biology early in an epidemic. Here, the authors assess forecasts of a suite of models during the Zika epidemic in Colombia, finding that the models that performed best changed over the course of the epidemic.